Induction of protective immune responses against schistosomiasis using functionally active cysteine peptidases - El Ridi, Rashika; Tallima, Hatem; Dalton, John P.; Donnelly, Sheila (Frontiers in Genetics, 2014)
Each year schistosomiasis afflicts up to 600 million people in 74 tropical and sub-tropical countries, predominantly in the developing world. Yet we depend on a single drug, praziquantel, for its treatment and control. There is no vaccine available but one is urgently needed especially since praziquantel-resistant parasites are likely to emerge at some time in the future. The disease is caused by several worm species of the genus Schistosoma. These express several classes of papain-like cysteine peptidases, cathepsins B and L, in various tissues but particularly in their gastrodermis where they employ them as digestive enzymes. We have shown that sub-cutaneous injection of recombinant and functionally active S. mansoni cathepsin B1 (SmCB1), or a cathepsin L from a related parasite Fasciola hepatica (FhCL1), elicits highly significant protection (up to 73%) against an experimental challenge worm infection in murine models of schistosomiasis. The immune modulating properties of this subcutaneous injection can boost protection levels (up to 83%) when combined with other S. mansoni vaccine candidates, glyceraldehyde 3-phosphate dehydrogenase (SG3PDH) and peroxiredoxin (PRX-MAP). This cysteine-treatment can also protect mice from S. haematobium infection. Here, we discuss these data in the context of the parasite’s biology and development, and provide putative mechanism by which the native-like cysteine peptidase induce protective immune responses.